Improving surveillance system and surgical site infection rates through a network: A pilot study from Thailand - Kasatpibal N. (2014)
Surveillance of surgical site infections (SSI) provides data upon which interventions to improve patient safety can be based. In Thailand, however, SSI surveillance has not yet been standardized.